Novel software for quantitative evaluation and graphical representation of masticatory efficiency. - Halazonetis, D J; Schimmel, M; Antonarakis, G S; Christou, P (J Oral Rehabil, 2013)
Blending of chewing gums of different colours is used in the clinical setting, as a simple and reliable means for the assessment of chewing efficiency. However, the available software is difficult to use in an everyday clinical setting, and there is no possibility of automated classification of the patient's chewing ability in a graph, to facilitate visualisation of the results and to evaluate potential chewing difficulties. The aims of this study were to test the validity of ViewGum - a novel image analysis software for the evaluation of boli derived from a two-colour mixing ability test - and to establish a baseline graph for the representation of the masticatory efficiency in a healthy population. Image analysis demonstrated significant hue variation decrease as the number of chewing cycles increased, indicating a higher degree of colour mixture. Standard deviation of hue (SDHue) was significantly different between all chewing cycles. Regression of the log-transformed values of the medians of SDHue on the number of chewing cycles showed a high statistically significant correlation (r² = 0.94, P < 0.01). ViewGum eliminates drawbacks of previous two-colour chewing gum test methods by the simplicity of its application. The newly developed ViewGum software provides speed, ease of use and immediate extraction of clinically useful conclusions to the already established method of chewing efficiency evaluation and is a valid adjunct for the evaluation of masticatory efficiency with two-colour chewing gum.
Keywords: Adult; Algorithms; Chewing Gum; Color; Computer Graphics; Female; Humans; Image Processing, Computer-Assisted; Male; Mastication; Software; Software Validation; Time Factors; User-Computer Interface; Young Adult